INFLUENCE OF PARAMETERS OF ONE-COMPONENT AND TWO-COMPONENT CARBON FILLER ON THE ELECTRICAL CONDUCTIVITY OF ACRYLIC POLYMER COMPOSITE COATING - КУРИПТЯ, Я. А.; СЕНИК, І. В.; БАРСУКОВ, В. З.; ХОМЕНКО, В. Г. (Technologies and Engineering, 2023)
Purpose. Research of the influence of the parameters of one- and two-component carbon filler on the electrical conductivity of acrylic polymer composite in the form of a thin coating. Methodology. Samples of composites were developed using a high-speed mixer. The size and shape of the filler particles, as well as the structure of polymer composites, were examined in reflected light using a microscope MBI-15U42. The electrical conductivity of the samples obtained was measured according to ASTM D257-07 and ASTM F1711-96 standards in accordance with the surface resistance of the samples. Findings. The percolation thresholds for composites, which were filled by a one-component filler – technical carbon, graphite KGP-C1, carbon fiber – were determined. As a result of the experiments, it was shown that the percolation behavior of the conductivity of polymer composites, filled with a single-component filler is related to the morphology of the corresponding filler and the internal structure that it forms when interacting with the polymer. Synthesized polymer composites with two-component fillers KGP-S/technical carbon or carbon fiber T300/technical carbon, and different ratios of them and total filling in the composite 50–70 vol. % showed a synergistic effect of electrical conductivity at a specific ratio of filler components. Originality. The relationship between the ratio of components of a carbon two-component filler and electrical conductivity of an acrylic polymer composite has been established. Practical value. The optimal pair of carbon fillers, their content and the ratio of the two-component filler in the acrylic polymer composite are determined.